Analysis of the state of tourism for the construction of sustainable strategies Vaupés, Colombia (Orinoquia, 2018)
It is sought to identify in the department of Vaupés the different opportunities, threats, strengths and weaknesses -in terms of tourism- by means of a diagnosis where a review is made addressing the political, cultural, environmental, geographical and historical to finalize with a model strategic adapted to six stages to develop; In the first stage the geographical location is observed and the areas with intensive, extensive and primitive activity have been indicated. During the second stage, a plan of the possible sites to be visited is demarcated in the corresponding map, the third phase makes emphasis on the architecture that should be used in the place for the development of tourism; said this the fourth stage establishes the mechanisms for the generation of income followed by the management and monitoring of the impact of visitors and ends with the aspects that naturalist guides should have. Thus, a descriptive and exploratory methodology was used to have a greater scope; the ecotourism development manual created by “The Nature Conservancy” was used; besides taking advantage of the ethnocultural technique as a base of the infrastructure supported by computerized processes for its design.
Keywords: Tourism; ethno; gastronomic tourism; FODA; strategies; tourist plan